2004
DOI: 10.1007/s00421-004-1059-8
|View full text |Cite
|
Sign up to set email alerts
|

Circadian rhythms in blood lactate concentration during incremental ergometer rowing

Abstract: This study examined whether circadian rhythms affect lactate threshold (Th(lac)) during rowing exercise. Eleven male, endurance-trained athletes [mean (SD) age 29.5 (6.1) years] rowed at 0200, 0600, 1000, 1400, 1800 and 2200 hours under the same experimental conditions. Capillary blood (25 microl) was obtained from the tip of the toe during the last 30 s of a continuous, multi-stage, 3-min, incremental protocol on the Concept II ergometer. To determine Th(lac), a curve-fitting procedure (the D(max) method), a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
1
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 19 publications
1
19
1
3
Order By: Relevance
“…In the literature we apply the cycle ergometer exercise at various times, such as: 2:00, 6:00, 10:00, 2:00pm, 6:00pm and 10:00pm and has been found that significant circadian variation in the Fc max [10]. Moreover, also the use of cycling were their used the time, 4:00, 8:00, 12:00, 3:00pm, 6:00pm, 9:00pm and 24:00 h [11], and in another study that found no significant differences between the different periods [5], used four times (8:00, 12:00, 4:00pm and 8:00pm) [5].…”
Section: Introductionmentioning
confidence: 99%
“…In the literature we apply the cycle ergometer exercise at various times, such as: 2:00, 6:00, 10:00, 2:00pm, 6:00pm and 10:00pm and has been found that significant circadian variation in the Fc max [10]. Moreover, also the use of cycling were their used the time, 4:00, 8:00, 12:00, 3:00pm, 6:00pm, 9:00pm and 24:00 h [11], and in another study that found no significant differences between the different periods [5], used four times (8:00, 12:00, 4:00pm and 8:00pm) [5].…”
Section: Introductionmentioning
confidence: 99%
“…Како главна причина за тоа се смета различната ензимска активност. Заради тоа тестовите треба да се направат и во двата дела на денот за да може да се направи разлика од добиените резултати [14].…”
Section: дискусијаunclassified
“…Interestingly, studies examining other indices of endurance capacity have demonstrated a circadian rhythm or diurnal variation suggesting evening superiority: higher oxygen consumption and heart rate at the lactate threshold intensity 39) , higher aerobic contribution to energy production during 30 seconds of maximal pedaling 40) , and a faster record in a 16.1 km cycling time trial (about 23 minutes) 41) .…”
Section: A Variety Of Human Circadian Rhythms and Characteristicsmentioning
confidence: 99%
“…Oxygen consumption and heart rate at the lactate threshold intensity 39) Time to exhaustion in the heat 42) 16.1-km cycling time trial 41) Short-term power output 27,28) No time of day variation Adverse cardiovascular events 45,46,55,56) Exercise-induced adverse cardiovascular events 57,58) Higher risk in the morning than in the afternoon and evening…”
Section: Safetymentioning
confidence: 99%